Land carrying capacity status and land utilization optimization strategy in South Sorong, Indonesia - Kondong, Hendrik; Kurniawan, Andri; Santosa, Langgeng Wahyu (Brawijaya University, 2025)
Economic growth is the key to community welfare, especially in rural areas. Using land wisely is a simple way to improve the community's economic quality. At its core, the issue is whether the available land can be used most effectively since lousy management can lead to land degradation. This study aimed to identify the status of land carrying capacity and various strategies that can be carried out to optimize land in South Sorong, Indonesia. A spatial approach was used to analyze existing land conditions. Furthermore, the carrying capacity status was identified by considering land availability and potential community needs. Pressure State Responsibility (PSR) analysis was used to identify solutions that can be employed to maximize land resources. Research findings showed that existing land in South Sorong is dominated by forests (40.04%), swamps (36.47%), and mangroves (13.02%). The land carrying capacity status in South Sorong has a surplus value, meaning that existing land is more than sufficient to meet the population's needs, which depends on its productivity. Land development and optimization can be carried out but must involve multiple stakeholders and be carried out in a planned and careful manner so that environmental sustainability is maintained. Land optimization strategies that can be done are intensifying agriculture, adding infrastructure, and introducing mechanical technology in land management. Finally, the finding can be used as a basis for policymakers, especially in rural areas where the land carrying capacity status is still surplus.